Ecological assessment of surface water quality in the upper Pripyat river basin based on hydrochemical indicators - Malovanyy, Myroslav; Boiaryn, Maria; Biedunkova, Olha; Voloshyn, Volodymyr; Netrobchuk, Iryna; Statnyk, Ihor (Ecological Questions, 2026)
The article presents the results of the ecological assessment of the surface water quality of the upper Pripyat River basin based on hydrochemical indicators, using the integral ecological index IE. The study covers the period from 2019 to 2023 and includes the analysis of water mineralization, physicochemical indicators, biogenic substances, trace elements and toxic pollutants in the Turia, the Vyzhivka, the Styr, the Stokhid, the Tsyr and the Pripyat rivers. Of the three analyzed components of water quality indicators (salt composition, tropho-saprobiological composition, and specific toxic substances), the tropho-saprobiological section which reflects the degree of organic pollution had relatively worse values. It was found that the main factors affecting the water quality of the studied rivers are discharges of untreated and poorly treated wastewater, agricultural pollution, as well as changes in the agricultural landscape.